A Legal Review of Informed Consent in Plastic Surgery Practice in Indonesia - Dewi Fibrini; Marice Simarmata; Irsyam Risdawati (DE LEGA LATA: JURNAL ILMU HUKUM, 2026)
Informed consent, as a statement of agreement by the patient in this therapeutic agreement, is considered valid if the patient expresses his or her will freely. Therefore, when a patient expresses his or her consent in the form of informed consent, the patient must express his or her will without any coercion, error, or deception. What we want to discuss here is that sometimes patients are not honest when asked for information regarding their actual condition by the doctor. This results in the doctor in performing medical procedures having to violate the informed consent agreement because the patient's condition makes it impossible to fulfill the informed consent agreement. Informed consent in medical procedures is one of the elements that must be fulfilled and serves as the basis for justification for medical procedures, especially for invasive medical procedures. Invasive medical procedures can basically be classified as acts of abuse as regulated in Article 351 of the Criminal Code. However, this categorization is removed if the medical procedure meets three justification elements: if the medical procedure is carried out in accordance with scientific knowledge and experience in the medical field; there is a concrete medical purpose; and there is informed consent. Informed consent becomes risky when the patient is in an emergency condition. Therefore, legal protection is needed for medical personnel. Legal protection for doctors in the context of health communication is also an important consideration. When a conflict arises between a doctor's obligation to provide accurate information and the obligation to maintain the confidentiality of patient medical data, doctors are often vulnerable to potential lawsuits. Law No. 17 of 2023 and other regulations provide legal protection for doctors by establishing limits on their obligations and rights in communicating with patients. This legal protection includes protection from unfounded lawsuits, dispute resolution mechanisms through mediation, and support for doctors in more complex medical consultations. Patient dishonesty can seriously impact the quality of medical care. If patients do not provide complete or accurate information, the risk of misdiagnosis or treatment errors increases significantly. The impact of these errors not only endangers the patient's health but also places doctors at risk of lawsuits or malpractice claims.